KEMAMPUAN MENULIS KARANGAN NARASI MELALUI MEDIA GAMBAR SISWA KELAS VIII SMP - Frederika F. Kwaar; Wimse R. Palar; Nontje J. Pangemanan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to describe students’ ability in writing narrative essays through the use of picture media among eighth-grade students at Rosa Delima Catholic Junior High School Tondano. The study employed a descriptive method with a qualitative approach. Data collection techniques included observation, interviews, and narrative writing tests. The research subjects consisted of seven eighth-grade students at Rosa Delima Catholic Junior High School Tondano. The focus of the study was directed at students’ ability to organize narrative structure, develop story ideas, use language features, and utilize picture media as a stimulus in narrative writing activities. The results showed that the students’ narrative writing ability achieved an average score of 71 and was categorized as fair. The use of picture media helped students develop ideas, organize story plots more coherently, and improve the use of temporal conjunctions and descriptive expressions in their writing. In addition, the learning atmosphere became more active and interactive because students could more easily understand the sequence of events through the pictures provided. However, several obstacles were still found, such as limited vocabulary, inaccurate spelling, and less optimal story development. Therefore, picture media can be used as an alternative learning medium to improve students’ narrative writing skills in Indonesian language learning. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan kemampuan menulis karangan narasi melalui penggunaan media gambar pada siswa kelas VIII SMP Katolik Rosa Delima Tondano. Penelitian menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan tes menulis narasi. Subjek penelitian terdiri atas tujuh siswa kelas VIII SMP Katolik Rosa Delima Tondano. Fokus penelitian diarahkan pada kemampuan siswa dalam menyusun struktur narasi, mengembangkan ide cerita, menggunakan unsur kebahasaan, serta memanfaatkan media gambar sebagai stimulus dalam menulis teks narasi. Hasil penelitian menunjukkan bahwa kemampuan menulis karangan narasi siswa memperoleh nilai rata-rata sebesar 71 dan termasuk dalam kategori cukup. Penggunaan media gambar membantu siswa mengembangkan ide, menyusun alur cerita secara lebih runtut, serta meningkatkan penggunaan konjungsi temporal dan deskripsi dalam tulisan. Selain itu, suasana pembelajaran menjadi lebih aktif dan interaktif karena siswa lebih mudah memahami urutan peristiwa melalui gambar yang diberikan. Meskipun demikian, masih ditemukan beberapa kendala, seperti keterbatasan kosakata, penggunaan ejaan yang kurang tepat, dan pengembangan isi cerita yang belum optimal. Dengan demikian, media gambar dapat digunakan sebagai alternatif media pembelajaran untuk meningkatkan keterampilan menulis narasi siswa pada pembelajaran Bahasa Indonesia.